Evaluating the impact of biochar on biomass and nitrogen use efficiency of sugarcane using 15N tracer method - Chen, Ge; Gui, Jie; Qing, Cui-Xian; Huang, Dong-Liang; Liao, Fen; Yang, Liu (Frontiers in Agronomy, 2022)
N is an essential nutrient for sugarcane (Saccharum spp. Hybribds) growth. Excess chemical nitrogen fertilizer applied still a serious problem of China sugarcane plant. Biochar has shown promise in improving crop yield and N use efficiency (NEU).However its impact on sugarcane is not well-studied. To investigate how biochar impacts on sugarcane growth and nitrogen N use efficiency (NUE), a glasshouse pot experiment was conducted using the 15N tracer method. Two cultivars, GT11 and B8, were chosen as test objects and were planted under low N(120 kg N hm-2) and high N(600 kg N hm-2)condition, respectively. The effects of low and high biochar application rates (10 t hm-2 and 20 t hm-2) on growth, nitrogen uptake, accumulation and distribution as well as NUE in GT11 and B8 were studied. Results showed that sugarcane biomass was not significantly affected by biochar application. N uptake by GT11 was significantly increased 23.91% - 45.42% by C20 and N120 condition at tillering stage and elongation stage. While N uptake by B8 showed a significant response to B10 and B20 with an increase of 27.27% and 30.40% at tillering stage,respectively. Biochar application led to 0.28% - 23.75% and 1.08% - 30.07% increase in NUE of GT11 and B8,respectively. The effect of biochar application of N from fertilizer(FF) was significant,however only C20 treatment shown remarkable response when under low N treatment. Our study suggest that the effects of biochar on sugarcane depend on varieties and the applied rate of biochar and N fertilizer.Biochar application with inorganic N could improve N uptake and N use of sugarcane.